Akibat Hukum Perbuatan Wanprestasi Dalam Perjanjian Hutang-Piutang - I Wayan Bandem; Wayan Wisadnya; Timoteus Mordan (Jurnal Ilmiah Raad Kertha, 2020)
Accounts payable is a practice of lending and borrowing generally in the formof money as the object of the loan that is done by someone with another person made inan agreement. The agreement itself has been regulated in the provisions of the Civil Code(Civil Code). In civil law the agreement has been regulated regarding the rights andobligations of the parties making the agreement. The party that gives the loan is calledthe creditor while the party that receives the loan is called the debtor. Creditors areentitled to fulfillment of achievements while debtors must carry out their achievements.However, in reality the legal relationship between creditors and debtors, especiallyregarding agreements, is often problematic so that defaults arise. Default is a negligentevent where a person does not carry out his performance or does not fulfill his obligationsaccordingly, thus causing harm to one party. This research is entitled "Legal Effects ofDefaults in the Debt Agreement (Civil Case Study Case No.638 / Pdt.G / 2017 / PN Dps).This study aims to find out how the legal consequences if defaulting and how judgesconsider in deciding default cases (Civil Case Study Case No.638 / Pdt.G / 2017 / PNDps). This research method uses a normative juridical method that is descriptive innature. Data sources consist of primary data, namely interviews and secondary data,namely primary, secondary and tertiary legal data. Methods of collecting data throughliterature studies and field studies (interviews), then the data is analyzed qualitatively.The results of the study concluded that the legal terms of the agreement were inaccordance with article 1320 of the Civil Code (KUHPerdata), namely the existence ofagreements, skills, objects or certain things, legal causes or causes as well as the article1338 Civil Code (KUHPerdata). Judges 'consideration in terminating the disputesbetween the creditors' debt agreement with the debtor in accordance with case No.638 /Pdt.G / 2017 / PN Dps is correct, namely by looking at the evidence both written evidenceand evidence from the parties. Based on the evidence attached to the trial the judgedecided to grant the plaintiff's claim and stated that the defendant was found guilty or indefault.